2013
DOI: 10.1007/978-1-4614-8289-5_5
|View full text |Cite
|
Sign up to set email alerts
|

Gadd45 in the Liver: Signal Transduction and Transcriptional Mechanisms

Abstract: Injury and growth stimulation both remarkably increase the hepatic expression of Gadd45β. In liver cancer, promoter methylation frequently silences Gadd45β, demonstrating due to a suppressive function that is often proapoptotic. This contrasts with normal hepatocytes, where Gadd45β facilitates cell survival, growth, and proliferation. Gadd45β binds MKK7-downstream of TNFα and its receptors-to prevent this kinase from activating JNK2. Hence, the Gadd45b-/- genotype increases cell injury and decreases cell proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…It is known that Gadd45α is up-regulated in response to DNA damage [3,4]. However, while DNA damage is a consequence of various cytotoxic stimuli, it is unclear whether Gadd45α induction is the result of DNA damage.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is known that Gadd45α is up-regulated in response to DNA damage [3,4]. However, while DNA damage is a consequence of various cytotoxic stimuli, it is unclear whether Gadd45α induction is the result of DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…However, while DNA damage is a consequence of various cytotoxic stimuli, it is unclear whether Gadd45α induction is the result of DNA damage. Additionally, the contribution of Gadd45α to apoptotic signaling is controversial [3,4]. Experiments using primary hepatocytes demonstrated that ER stress is an early inducer of Gadd45α.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The level of downregulation of growth arrest DNA damage-inducible gene 45β (GADD45b) in HCC is strongly correlated with increased tumor malignancy [5]. GADD45β is associated with cell growth control, apoptosis and cellular responses to DNA damage [6]. Consequently, lack of GADD45β expression in HCC might lead to atypical cell growth or apoptosis.…”
Section: Introductionmentioning
confidence: 99%